Portable temperature and humidity detector - ZHAO YONGLING; ZUO CHENGUANG; CHEN MO; DU DAN; WANG YUWEI (2024)
The utility model discloses a portable temperature and humidity detector which comprises a shell, a detection head is arranged outside the shell, a connecting wire is connected between the detection head and the shell, a storage assembly is arranged on the rear surface of the shell and comprises a storage block, a limiting block is arranged on the rear surface of the storage block, and the limiting block is arranged on the limiting block. A wiring groove is formed in the inner wall of the opening of the limiting block and extends to the outside of the storage block; the rotating piece is arranged in the limiting block, the bottom of the rotating piece is connected with the connecting line in a clamped mode, the rotating piece comprises a rotating disc, a bottom column is fixed to the bottom end face of the rotating disc, and a clamping groove is formed in the bottom end face of the bottom column; through the designed storage assembly, the connecting wire can be stored, the occupied space is reduced, carrying